Lingual Form of Unifier of Social Harmony Javanese Coastal Community in Semarang - Suryadi M.; Astutii Sri Puji; Supatra Hendarto; Faza Surya Rusyda Hana (E3S Web of Conferences, 2020)
This study is aimed to describe the lingual forms of Javanese speakers of the Semarang people, as one of the representatives of the Javanese community in the coastal areas. The form of lingual is in the form of lingual units of greetings as a means of unifiers in social life and part of the harmony of social life.The location of the research is in Semarang City. The selection of respondents and informants uses a purposive sampling system. The method of data collection is done through structured interviews, in-depth interviews, and focus group discussions. The method of data analysis uses three basic components of meaning: word-concept-referent through the paradigm of linkages between lingual-cultural-behaviour relationships. The findings of the study are the wealth of lingual forms of the Javanese coastal community of Semarang City in the form of semantic relations and forms, which are framed by the culture of coastal communities. So t and uniqueness of social gradation.